Hyperferritinemia as a Prognostic Factor for Immunosuppression in Patients with Acquired Immunodeficiency Syndrome - Palencia, Laura; Villalobos Perozo, Rafael (Kasmera, 2011)
A prospective study was carried out to determine if hyperferritinemia is a predictive factor for immunosuppression in patients with acquired immunodeficiency syndrome (AIDS). The population consisted of 40 patients hospitalized at the University Hospital of Maracaibo (Hospital Universitario de Maracaibo), from January to October, 2010. Twenty-seven (67.50%) patients were male and 13 (32.50%) were female. 22.50% had a T CD4+ lymphocyte count between 200-400 cells/mm3 with a mean ferritin of 144.2 ± 127.1 ng/mL; 77.50% had a T CD4+ lymphocyte count of <200 cells/mm3 and a ferritin average of 1100.0 ± 984.7 ng/mL (p = 0.01). An inverse negative correlation was found between high ferritin levels and low T CD4+ lymphocyte count (r = 0.3135, p= 0.030), low numbers of leukocytes (r = 0, 7458 p = 0.012), low levels of protein (r = 0.5814, p =0.01), and a directly proportional relation with the increase of ESR (r = 0.7422, p = 0.001). In patients who died, the mean ferritin level (1180.0 ± 1,072) statistically (p = 0.018) was higher compared with the average ferritin level (474 ± 440.2) of patients who survived. Conclusions are that these results are sufficiently relevant to take hyperferritinemia into account as a prognostic factor for the immunosuppression of diagnosed AIDS patients.